Catalytic Activity of LDH-TiO2 and LDH-ZnO in Photodegradation of Procion Red - Nova Yuliasari; Amri Amri; Risfidian Mohadi; Elfita Elfita; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Pristine layered double hydroxides (LDHs) which have been modified into LDHs-metal oxide composite were applied as procion red (PR) photodegradation catalysts. The preparation was performed using a low calcination temperature of 300°C. Optimization variations include pH, catalyst weight and catalysis time. The degradation percentages of Mg/Al LDH, Mg/Al-TiO2 and Mg/Al-ZnO were 51.8%, 72.0% and 89.5%, respectively. The percentage of degradation of Zn/Al LDH, Zn/Al-TiO2 and Zn/Al-ZnO were 44.0%, 61.2% and 58.4%, respectively. The study results showed that all composites produced a greater percentage of PR degradation and better reusability than pristine LDH. Mg/Al LDH-based catalysts tend to catalyze PR better than Zn/Al LDH-based catalysts. PR which is an anionic dye when photodegraded using Mg/Al-ZnO tends to be better than Mg/Al-TiO2 meanwhile Zn/Al-TiO2 and Zn/Al-ZnO have competitive performance.